Profitability of Logistics Companies: Empirical Evidence of Accounts Receivable Turnover and Operating Cash Flow Ratio - Herni Supartika; Taufik Sadikin; Farid Arifin (Lembaga Pengembangan Kinerja Dosen, 2026)
The commercial resilience of the domestic distribution network depends heavily on its logistical infrastructure, yet global disruptions spanning from 2020 to 2024 exposed this framework to severe systemic shocks. This investigation interrogates the empirical dependencies of asset utilization yield against fluctuations in capital reclamation cycles and operational liquidity cushions within public freight enterprises listed on the Indonesia Stock Exchange (IDX). Methodologically motivated by structural disparities and divergent empirical findings in existing literature, this inquiry deploys a quantitative design using descriptive diagnostics and empirical verification. From a foundational universe of 19 logistics corporations, purposive sampling isolated a subset of 10 entities, yielding 50 panel observation units extracted from audited financial disclosures. The structural estimation relies on a pooled ordinary least squares architecture, validated through restricted residual sum of squares testing and score-based multiplier diagnostics executed via EViews 12. To safeguard statistical inference, the underlying error structure underwent exhaustive validation, including normality, multi-variable collinearity, cross-sectional heteroscedasticity, and first-order serial dependency metrics. The resulting parametric estimates reveal that the velocity of outstanding credit collection exerts a highly robust positive pressure on asset-based returns, whereas the metric evaluating core cash generation against immediate obligations fails to manifest a statistically meaningful linkage. Simultaneously, both financial dimensions interact to exert a joint structural impact on corporate returns, capturing an adjusted variance portion of 38.15%. Ultimately, these dynamics clarify that rigorous credit lifecycle optimization serves as the primary engine for capital returns within this industry.